2022
DOI: 10.1155/2022/9056363
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Platelet to Lymphocyte Ratio in Sepsis: A Systematic Review and Meta-analysis

Abstract: The goal of this study was to conduct a systematic review of the literature on the relationship between peripheral blood platelet to lymphocyte ratio (PLR) and mortality in sepsis and to integrate the findings in a meta-analysis. An electronic search of three main databases was performed: PubMed, Embase, and Scopus on 19 December 2021. Finally, 16 studies comprising 2403 septic patients, including 1249 survivors and 1154 nonsurvivors, were included in this meta-analysis. We found that PLR levels were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 73 publications
(119 reference statements)
0
18
1
1
Order By: Relevance
“…Therefore, a high platelet-tolymphocyte ratio (PLR) is a promising biomarker for predicting sepsis severity. 20,21 As information from a complete blood count could be helpful in predicting the severity and mortality of various inflammatory disorders, while the prognostic factors in SCARs are still unclear or rely on integrated clinical and laboratory parameters, our study aims to explore whether the data from a basic laboratory assessment could help to predict the HMR in SCAR patients of all phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a high platelet-tolymphocyte ratio (PLR) is a promising biomarker for predicting sepsis severity. 20,21 As information from a complete blood count could be helpful in predicting the severity and mortality of various inflammatory disorders, while the prognostic factors in SCARs are still unclear or rely on integrated clinical and laboratory parameters, our study aims to explore whether the data from a basic laboratory assessment could help to predict the HMR in SCAR patients of all phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation also plays a role in the worsening coagulation disorders in systemic inflammatory reactions, and lymphopenia could reflect the immunosuppressive status in severe infections. Therefore, a high platelet‐to‐lymphocyte ratio (PLR) is a promising biomarker for predicting sepsis severity 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…This is also consistent with our results. In addition, a meta-analysis on the prognostic value of PLR in sepsis [39] showed that high PLR predicts worse prognosis. These are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…NLR is now widely used in all medical disciplines and is considered to be able to reflect body’s reaction to various external or internal stimuli, and the normal value of NLR was considered to be 1.0–2.0 [ 51 ]. Similarly, PLR also showed potential value in multiple diseases [ 52 , 53 ] and the normal value of PLR was 70–200 [ 51 ]. These indices are calculated from common blood cell count, and the mechanisms behind them are thought to be results of cell functions, including those of neutrophils, lymphocytes, and platelets.…”
Section: Discussionmentioning
confidence: 99%